PENGARUH SOSIALISASI PAJAK, KESADARAN WAJIB PAJAK, DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN DI DESA LAKEKUN KECAMATAN KOBALIMA KABUPATEN MALAKA - Thomas Richardson Freitas Asa; Sarlin P. Nawa Pau; Siprianus G. Tefa (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2026)
This study aims to examine "the influence of tax socialization, taxpayer awareness, and tax sanctions on taxpayer compliance in paying Land and Building Tax (PBB) in Lakekun Village, Kobalima District, Malaka Regency". This study applies a quantitative approach with a survey method. Primary data were collected by distributing questionnaires to PBB taxpayers registered in Lakekun Village. The data analysis technique used was multiple linear regression with the help of SPSS analysis tools. The findings of this study Indicate that individually, tax socialization does not have a significant effect on taxpayer compliance, while tax awareness and sanctions have a significant effect on taxpayer compliance. Simultaneously, tax socialization, taxpayer awareness, and tax sanctions influence taxpayer compliance in paying PBB. This study is expected to be aconsideration for local governments in formulating tax policies, especially in efforts to improve PBB taxpayer compliance.